(untitled) (Research, Society and Development, 2021)
This research is qualitative in nature, bibliographical in nature, focusing on the practice of research in the history of education, according to the guidelines suggested by Luca (2020). This article addresses the images of pedagogical practices and the teacher-student relationship in the Brazilian school environment in the nineteenth century, brought by fiction literature, with emphasis on the novel genre. The methodology was developed in two stages, integrated with each other. In the first, three novels published in the 19th century were selected: Posthumous Memoirs by Brás Cubas and Conto de Escola, by Machado de Assis; The Athenaeum, by Raul Pompéia; O Coruja, by Aluísio Azevedo and A Normalista, by Adolfo Caminha. In the second stage, after the analytical reading of each of the works, passages in the narrative that translate the images of situations in the Brazilian school environment were pointed out, identifying the practices and the teacher-student relationship. In each analysis it was possible to identify passages that denote the existing school model. The research findings reinforce the multiple views of the aforementioned writers who, through their works, point to the configuration and reconfiguration of the educational system, against the political design of a Brazilian republican project.